Proses Seeding Dan Aklimatisasi Kultur Tercampur Pada Pengolahan Anaerob Limbah Cair Produksi Minyak Sawit - Gusti Rahayu; David Andrio; Nina Veronika (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Palm Oil Mill Effluent (POME) was high strength organic wastewater contained COD 50.000 – 70.000 mg/l. Mixed cultures used in this research is from cow dung. To increase concentration of bacteria on the inokulum and decreased lag phase on anaerobic treatment for treat it, the anaerobic mixed culture bacteria should be seeding process and acclimatized toward POME. The bioreactor of seeding process and acclimatization using circulating batch reaktor with worked volume 15 L and 5 L, respectively. Ratio wastewater to biomass bacteria was 70:30 (% V/V). This study use 3 variation of heat temperature of mixed culture anaerob that is 35° C for 1 hour; 70° C for 30 minutes; 100o C for 15 minutes with control. The parameter observed in this research was VSS and COD. Seeding process was doing in 5 days with highest VSS on day’s 5 was 8.280 mg/L and COD total concentration was 36.454 mg/L. Acclimatization process was doing on three stages, each of the 5 days. The most increase of VSS at the third stages of acclimatization was found within R1 (heat pretreatment inoculum 35° C for 1 hour) was 880 mg/L/day and the most reduction of soluble COD was found within R3 (heat pretreatment inoculum 100° C for 15 minutes) was 14,30%. Keywords : POME, mixed culture, circulating batch reactor,seeding, acclimatization, COD, VSS,